2020
DOI: 10.1038/s41598-020-71828-8
|View full text |Cite
|
Sign up to set email alerts
|

Greenbug (Schizaphis graminum) herbivory significantly impacts protein and phosphorylation abundance in switchgrass (Panicum virgatum)

Abstract: Switchgrass (Panicum virgatum L.) is an important crop for biofuel production but it also serves as host for greenbugs (Schizaphis graminum Rondani; GB). Although transcriptomic studies have been done to infer the molecular mechanisms of plant defense against GB, little is known about the effect of GB infestation on the switchgrass protein expression and phosphorylation regulation. The global response of the switchgrass cultivar Summer proteome and phosphoproteome was monitored by label-free proteomics shotgun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 87 publications
1
17
0
Order By: Relevance
“…The protein concentration was determined using the CB-X protein assay kit. One hundred μg of protein in 10 μl of the urea solution was diluted and digested with 1 μg trypsin (1:100 enzyme to substrate ratio) for 16 h overnight, and then an additional 1 μg of trypsin was added and digestion was continued for a further 3 h. Five hundred ng of each of the 9 secreted protein samples and 1 μg of each of the cytoplasmic protein samples was run by nano LC-MS/MS using a 2 h gradient on a 0.075 mm by 250 mm C 18 Waters CSH column feeding into a Q-Exactive HF mass spectrometer as described previously ( 49 ). All MS/MS samples were processed using Proteome Discoverer 2.2 software (Thermo) linked to the Mascot Server MS/MS search software (Matrix Science, London, UK, version 2.6.1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein concentration was determined using the CB-X protein assay kit. One hundred μg of protein in 10 μl of the urea solution was diluted and digested with 1 μg trypsin (1:100 enzyme to substrate ratio) for 16 h overnight, and then an additional 1 μg of trypsin was added and digestion was continued for a further 3 h. Five hundred ng of each of the 9 secreted protein samples and 1 μg of each of the cytoplasmic protein samples was run by nano LC-MS/MS using a 2 h gradient on a 0.075 mm by 250 mm C 18 Waters CSH column feeding into a Q-Exactive HF mass spectrometer as described previously ( 49 ). All MS/MS samples were processed using Proteome Discoverer 2.2 software (Thermo) linked to the Mascot Server MS/MS search software (Matrix Science, London, UK, version 2.6.1).…”
Section: Methodsmentioning
confidence: 99%
“…The data were searched using a decoy database to set the false discovery rate to 1% (high confidence). The protein quantification was processed as described previously ( 49 ). The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE ( 50 ) partner repository with the data set identifier PXD023039.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Septima with respect to Quintus at the control (70% SWC) as well as severe drought (40% SWC) revealed an enhanced relative abundance in spot 3803 identified as lipoxygenase-2 and ssp 3503 identified as aldehyde dehydrogenase 7b which are involved in the detoxification of lipid peroxides that arise as products of hydrogen peroxide reaction with unsaturated fatty acids. In the study of Zogli et al. (2020) , four lipoxygenases were identified in the response of switchgrass ( Panicum virgatum ) to greenbug infestation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more than 100 papers corresponding to “plant proteome and aphid” have been found in the Web of Science database (accessed in June 2022). Aphids induced the accumulation of several defense modulators such as terpene synthase, papain-like cysteine protease, serine carboxypeptidase, and lipoxygenase and the repression of photosynthesis-related proteins in plants ( Zogli et al., 2020 ). Nguyen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a number of studies (Bilgin et al, 2010;Singh et al, 2013), there is usually a decrease in the intensity of metabol-ic processes (including a decrease in the rate of protein synthesis) under conditions of biotic stress; it has a protective nature, thus keeping a vital potential of cells necessary for subsequent repair. In addition, it has been reported (Zogli et al, 2020) that Schizaphis graminum (Rondani, 1852) (Hemiptera) feeding on the leaves of Panicum virgatum L. inhibits the accumulation of proteins involved in photosynthesis. In our study, it was shown that accumulation of soluble protein content was observed in most plantings and, especially, in age group І.…”
Section: а вmentioning
confidence: 99%